3D Video Analysis and Its Application in Developmental and Educational Psychology Teaching. (14th May 2022) - Chen, Zhicheng; Ding, Lulu
Abstract : With the rapid development of information technology and network technology and the new requirements of education and teaching in the new era, 3D video technology has been more and more widely used in the field of education and teaching. Educational psychology plays a positive role in the field of education. Applying its relevant theories to classroom teaching is not only conducive to the establishment of a good teacher-student relationship but also helps teachers to understand the psychological characteristics and learning process of students, so as to greatly improve the quality of teaching. Therefore, this article is based on 3D video analysis technology, through the observation of the teaching video and coding, the verbal interaction between teachers and students' lines of code and data analysis, mainly to its frequency, specific length and single length data used for analysis, explores the lesson for the current situation of the teaching video case teacher's teaching behavior, commonness, and difference. From the perspective of learner psychology, the model of teacher's teaching behavior in MOOCs teaching video is constructed. On the other hand, from the perspective of coding system and learner psychology, this paper proposes the improvement strategies of teachers' teaching behavior in MOOCs teaching videos in China. The results show that the application of 3D video analysis method and educational psychology in student education can improve student work efficiency.